Pelatihan Pemanfaatan Teknologi Augmented Reality dan Virtual Reality Sebagai Media Pembelajaran Inovatif bagi Guru di SMP Negeri 10 Parepare - Rafrin, Mardhiyyah; Maharani, Putri Ayu; Muh. Agus; Amar, Muh. Ikhsan; Intizhami, Naili Suri; Nuranti B, Eka Qadri; Bahar, Nur Aini Sri Oktaviani; Armansyah, Muhammad Dicky; S., St. Aisyah; Kandi, Damar; Malika, Saphira Nur (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service program aims to enhance teachers’ skills in utilizing AR and VR technologies as innovative instructional media in the classroom. The program was implemented using a structured training model involving 20 teachers from SMPN 10 Parepare. The evaluation instrument consisted of a questionnaire, and the responses were analyzed using descriptive techniques. The results show that the training was highly aligned with teachers’ needs at the school (average response score: 4.75), easy to follow (4.66), very beneficial in improving the quality of learning (4.85), and motivating for teachers to adopt AR and VR technologies in their instructional practices (4.58). Overall, this training activity provided a significant contribution to enhancing teachers’ digital literacy, particularly in the use of innovative learning media.